2020
DOI: 10.1111/hsc.13216
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of family nurses among residents of a midsize eastern European city: A population‐based cohort study in Poland

Abstract: To improve the quality of care, patients' needs and expectations must be understood, and this can be achieved through learning their attitudes and expectations connected with using health services. The main aim of this study was to describe and analyse Białystok residents' expectations of family nurses. This cohort study was carried out in association with the ongoing project "Bialystok PLUS" in Poland. The respondents (n = 412) were administered a multiple-choice questionnaire concerning family nurses and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Researchers in Jordan (Almhdawi et al, 2022) where in their research there are several aspects have to be taken into account. Researchers from Poland have raised several aspects influencing health self-assessment in cities of Poland (Marcinowicz et al, 2022) and researchers have found that differences are noticed for this aspect of health self-assessment in rural areas of Poland (Stelmach et al, 2004). Researchers have concluded that family life and life-style influence health self-assessment in urban and rural areas (Glendinning, 1998).…”
Section: Theoretical Findingsmentioning
confidence: 99%
“…Researchers in Jordan (Almhdawi et al, 2022) where in their research there are several aspects have to be taken into account. Researchers from Poland have raised several aspects influencing health self-assessment in cities of Poland (Marcinowicz et al, 2022) and researchers have found that differences are noticed for this aspect of health self-assessment in rural areas of Poland (Stelmach et al, 2004). Researchers have concluded that family life and life-style influence health self-assessment in urban and rural areas (Glendinning, 1998).…”
Section: Theoretical Findingsmentioning
confidence: 99%